Multicomponent Reactions for de Novo Synthesis of BODIPY Probes: In Vivo Imaging of Phagocytic Macrophages - Vázquez-Romero, Ana (J Am Chem Soc, 2013)
Multicomponent reactions are excellent tools to generate complex structures with broad chemical diversity and fluorescent properties. Herein we describe the adaptation of the fluorescent BODIPY scaffold to multicomponent reaction chemistry with the synthesis of BODIPY adducts with high fluorescence quantum yields and good cell permeability. From this library we identified one BODIPY derivative (PhagoGreen) as a low-pH sensing fluorescent probe that enabled imaging of phagosomal acidification in activated macrophages. The fluorescence emission of PhagoGreen was proportional to the degree of activation of macrophages and could be specifically blocked by bafilomycin A, an inhibitor of phagosomal acidification. PhagoGreen does not impair the normal functions of macrophages and can be used to image phagocytic macrophages in vivo.